CALENDAR OF IMMUNOPROPHYLAXIS IN SECOND DECADE XXI CENTURY - V.К. Tatochenko (Вопросы современной педиатрии, 2010)
Perfection of Immunization Calendar during last 15 years had resulted in ending of poliomyelitis and elimination of measles, and sharply decreasing of morbidity with diphtheria, hepatitis B, rubella, parotitis, in a less degree — with whooping cough and tuberculosis. Morbidity with seasonal influenza was reduced too. These achievements must not hide from view the necessity of inclusion of vaccination against hemophilic and pneumococcal infections, chicken pox, papilloma virus and rotavirus, effectively used in developed countries. Widening of Calendar sharpens question of penta- and hexavaccines use, otherwise the number of needed injections can become outrageous. Author describes possible schemes of vaccination in infants with the use of combined vaccines, registered in Russia. Also the data on frequency of vaccination complications in Russia is presented.Key words: children, vaccination, Immunization Calendar.(Voprosy sovremennoi pediatrii — Current Pediatrics. – 2010;9(3):81-87)